Simbolisasi Warna dalam Al-Quran - Hamdan Hidayat (MAGHZA, 2020)
This article aims to discuss the symbolization of colors in the Qur'an. In the article, the symbolism of colors in the Qur'an is discussed using the thematic interpretation theory pioneered by Abdul Hay al-Farmawi. Through this thematic interpretation, theory found 6 colors found in the Koran, namely red, yellow, green, blue, black, and white scattered in 33 ayat contained in 22 surahs by mapping the results of research using thematic analysis techniques. The results of color research in the Qur'an are expressions that are marked with color in various forms of lafadz as a symbol to describe certain objects in a situation, situation, place, and nature of the object. First, read as a symbol of the beauty of nature. Second, yellow is a symbol of the image of humans in the world. Third, green is a symbol of fertile earth. Fourth, blue as a symbol of the human condition on the Day of Judgment. Fifth, black is a symbol of human images on the Day of Judgment. Sixth, white is a symbol of a human image when in heaven. The existence of this article shows that color is a simple but meaningful symbol hidden in the Qur'an which needs to be studied.